Institute of mediation in the mechanism for solving legal disputes: main ideas and principles - Podkovenko, Tetiana; Fihun, Natalia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
A definition of mediation is grounded in the article, the features of mediation dispute resolution procedure is analyzed. Attention is also paid to the preparation and participation of mediator in the negotiation process. Moreover, the authors review problems of legislative provision of mediation in Ukraine and outline their solutions